(3GdGOGQI GdeGdjI (B/s - (3MOGO, aGjR Sdjes ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2010)
(3OhQ h HjFI GdGOGQI GdeGdjI ,JbQjQ GdeSGgejf h GdbhGFe GdeGdjI ,JMdjd GdbhGFe GdeGdjI ,GdbjeI GdRefjI ddfbhO , GdYGFO h GdeNGWQ , eYOdGJ GdaGFOI h Jbjje GdSfOGJ , Jbjje GdCSge , CSGdjH GdehGRfI GdQCSeGdjI , JcdaI QCS GdeGd , gjcd QCS GdeGd h GdQaY , SjGSI JhRjY GdCQHGM , EOGQI QCS GdeGd GdYGed , EOGQI GdfbOjI , EOGQI GdPee GdeOjfI h GdeNRhf , GdJNWjW GdeGdj Whjd GdCLd(B.s
(3eQGLY U(B.420 (3; LOGhd U(B.424s
Keywords: (3GdGOGQI (B-(3GdeGdjIs; (3GdGbJUGO GdeGdjs; (3GdeGdjIs